Tobacco use disorder and the lungs. (26th November 2020) - McRobbie, Hayden; Kwan, Benjamin
Abstract: This narrative review provides a summary of the impact of tobacco smoking on the respiratory system and the benefits of smoking cessation. Tobacco smoking is one of the leading preventable causes of death world‐wide and a major risk factor for lung cancer and chronic obstructive pulmonary disease. Smoking is also associated with an increased risk of respiratory infections and appears to be related to poorer outcomes among those with COVID‐19. Non‐smokers with second‐hand smoke exposure also experience significant adverse respiratory effects. Smoking imposes enormous health‐ and non‐health‐related costs to societies. The benefits of smoking cessation, in both prevention and management of respiratory disease, have been known for decades and, to this day, cessation support remains one of the most important cost‐effective interventions that health professionals can provide to people who smoke. Cessation at any age confers substantial health benefits, even in smokers with established morbidities. As other treatments for chronic respiratory disease advance and survival rates increase, smoking cessation treatment will become even more relevant. While smoking cessation interventions are available, the offer of these by clinicians and uptake by patients remain limited.